2020
DOI: 10.1111/jon.12723
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity and Structural Disruption in the Default‐Mode Network Predicts Cognitive Rehabilitation Outcomes in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSEEfficacy of restorative cognitive rehabilitation can be predicted from baseline patient factors. In addition, patient profiles of functional connectivity are associated with cognitive reserve and moderate the structure‐cognition relationship in people with multiple sclerosis (PwMS). Such interactions may help predict which PwMS will benefit most from cognitive rehabilitation. Our objective was to determine whether patient response to restorative cognitive rehabilitation is predictable fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…The NeMo Tool uses a database of healthy tractograms on which the MS‐related lesion masks are superimposed to estimate the resulting regional disconnectivity pattern, that is, the percent of WM streamlines connecting to that region that also passes through a lesion. This approach has been used by our group and others to relate lesion‐related structural disconnectivity patterns to impairments, outcomes, functional connectivity disruptions, rehabilitation response, and gray matter pathology in pwMS (Fuchs, Carolus et al., 2018 ; Fuchs, Dwyer et al., 2018 ; Fusch et al., 2020 ; Kuceyeski et al., 2015 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NeMo Tool uses a database of healthy tractograms on which the MS‐related lesion masks are superimposed to estimate the resulting regional disconnectivity pattern, that is, the percent of WM streamlines connecting to that region that also passes through a lesion. This approach has been used by our group and others to relate lesion‐related structural disconnectivity patterns to impairments, outcomes, functional connectivity disruptions, rehabilitation response, and gray matter pathology in pwMS (Fuchs, Carolus et al., 2018 ; Fuchs, Dwyer et al., 2018 ; Fusch et al., 2020 ; Kuceyeski et al., 2015 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the bilateral PCUN, the PCC, right PHG, and right MTG exhibit a significant decreased group difference. Recent research revealed that PCC and PCUN appeared to have the most structural and functional alterations in MCI patients (Fuchs et al, 2020). From the structural point of view, a study highlighted the association between PHG and gait parameters in MCI patients.…”
Section: Interactive Neural Networkmentioning
confidence: 99%
“…cutoff values (6,7) or latent profile analysis (8). Furthermore, the involvement of cognitive reserve has been suggested to partly explain the "clinicoradiological paradox" in MS patients without CI despite the evidence of brain damage (9)(10)(11)(12)(13).…”
Section: Primary Progressive Ms (Ppms)mentioning
confidence: 99%